Vascular Anomalies Caused by Abnormal Signaling within Endothelial Cells: Targets for Novel Therapies - Nguyen, Ha-Long; Boon, Laurence M.; Vikkula, Miikka (Seminars in Interventional Radiology, 2017)
Vascular anomalies arise as a consequence of improper development and maintenance of the vasculature. Our knowledge on the pathophysiological bases of vascular anomalies has skyrocketed during the past 5 years. It is becoming clear that common intracellular signaling pathways are often activated by mutations, causing endothelial cell dysfunction. These mutations cause hyperactivation of two major intracellular signaling pathways that may be controlled by inhibitors developed for cancer treatment. Although we do not know yet all the downstream effects, it has become evident that normalization of the abnormal signaling is an interesting target for therapy. This is a major paradigm change, as developmental malformations were considered to be inert to any molecular treatment.
Keywords: vascular malformations; mutations; interventional radiology